Response of a bridge isolated with FPS to earthquake ground motion - Krishnamoorthy, A. (Journal of Structural Engineering, 2024)
Friction pendulum system (FPS) with spherical sliding surface is an effective isolation system for bridges subjected to earthquake ground motion. The sliding surface of the FPS is spherical so that the gravitational force will provide a restoring stiffness that helps to bring back the superstructure to its original position after the earthquake. In this paper, the seismic response of a continuous bridge isolated with FPS subjected to earthquake ground motion is studied. In the analysis, superstructure, sliding bearing and pier are considered as one unit. Sliding bearing is modeled as a fictitious spring with large value of stiffness during non sliding phase and zero stiffness during sliding phase. The bridge is subjected to El Centro earthquake ground motion and the sliding displacement of the superstructure and base shear of pier is obtained at various time intervals. In order to study the effects of isolation, the response of the isolated bridge is compared to the response of a non-isolated bridge for similar conditions. In addition, the effect of coefficient of friction of sliding material on response of the isolated bridge is also studied. It is concluded from the study that the isolation with FPS reduces the base shear response of the bridge considerably without much increase in sliding and residual displacements.